Analisis Pengaruh Sinar Matahari Terhadap Pewarna Alami pada Citra Kain Tenun - Bunga Jawan, Modestine; Batarius, Patrisius; Tedy, Frengky (LPPM UNIKA Santo Thomas, 2022)
Woven cloth is one of the local cultural heritages that is still being preserved and is part of the typical handicrafts of the Indonesian people which can be found in various regions. In general, the colors found in woven fabrics are made using natural dyes and some are made with artificial dyes. The color motifs found on woven fabrics describe the quality of this type of cloth, but the dyes on woven fabrics will also experience discoloration quickly when dried directly in the sun. In this study, experiments were carried out on woven fabrics using natural dyes, with the drying process starting at 10.00-16.00 and taking each image sample every 1 hour. To measure image quality which is an indication that there is a decrease in color in the image of woven fabrics using natural dyes, it is done using Matlab software. The results of this study are in the form of color changes which can be seen from the calculation data in the form of RGB values, Histograms as well as MSE and PSNR values.